Increased Hippocampal Neurogenesis and p21 Expression in Depression: Dependent on Antidepressants, Sex, Age, and Antipsychotic Exposure - Epp, Jonathan R (Nature Publishing Group, 2013)
The mammalian hippocampus continues to generate new neurons throughout life. The function of adult-generated neurons remains controversial, but adult neurogenesis in the hippocampus is related to depression. Studies show that neurogenesis in the hippocampus is regulated by antidepressants in both humans and rodents, but no studies have examined the effects of age, sex, or antipsychotic exposure on the relationship between depression, antidepressant exposure, and hippocampal neurogenesis in humans. Hippocampal sections were obtained from the Stanley Medical Research Institute and were immunohistochemically labeled for the immature neuron marker doublecortin and the cell cycle arrest marker p21. We compared the number of cells in the granule cell layer and subgranular zone that expressed these proteins in brains from control subjects (n=12), patients with major depressive disorder (MDD) without psychotic symptoms (n=12), and patients with MDD and psychotic symptoms (n=12). We show here that the density of doublecortin/NeuN expression was increased in MDD patients compared with controls and MDD patients with psychosis, with the effect greater in women. Further, we show that older depressed patients without psychosis had higher levels of p21/NeuN expression and that depressed individuals prescribed antidepressants had higher levels of p21/NeuN expression, but only in older women. We show for the first time that changes in neurogenesis due to prescribed antidepressants or depression are dependent on age, sex, and the presence of antipsychotics or psychotic symptoms.